Casein kinase II phosphorylates I kappa B alpha at S-283, S-289, S-293, and T-291 and is required for its degradation. - McElhinny, J A (1996)
The phosphoprotein I kappa B alpha exists in the cytoplasm of resting cells bound to the ubiquitous transcription factor NF-kappa B (p50-p65). In response to specific cellular stimulation, I kappa B alpha is further phosphorylated and subsequently degraded, allowing NF-kappa B to translocate to the nucleus and transactivate target genes. To identify the kinase(s) involved in I kappa B alpha phosphorylation, we first performed an I kappa B alpha in-gel kinase assay. Two kinase activities of 35 and 42 kDa were identified in cellular extracts from Jurkat T and U937 promonocytic cell lines. Specific inhibitors and immunodepletion studies identified the I kappa B alpha kinase activities as those of the alpha and alpha' subunits of casein kinase II (CKII). Immunoprecipitation studies demonstrated that CKII and I kappa B alpha physically associate in vivo. Moreover, phosphopeptide maps of I kappa B alpha phosphorylated in vitro by cellular extracts and in vivo in resting Jurkat T cells contained the same pattern of phosphopeptides as observed in maps of I kappa B alpha phosphorylated in vitro by purified CKII. Sequence analysis revealed that purified CKII and the kinase activity within cell extracts phosphorylated I kappa B alpha at its C terminus at S-283, S-288, S-293, and T-291. The functional role of CKII was tested in an in vitro I kappa B alpha degradation assay with extracts from uninfected and human immunodeficiency virus (HIV)-infected U937 cells. Immunodepletion of CKII from these extracts abrogated both the basal and enhanced HIV-induced degradation of I kappa B alpha. These studies provide new evidence that the protein kinase CKII physically associates with I kappa B alpha in vivo, induces multisite (serine/threonine) phosphorylation, and is required for the basal and HIV-induced degradation of I kappa B alpha in vitro.